Maternal death causes before and during COVID-19 pandemic: a descriptive study in Banjarnegara Indonesia - Purwatiningsih, Yuni; Sunaryo; Lestyoningrum, Sinta Dewi (Universitas Gadjah Mada, 2023)
Purpose: Maternal mortality in Indonesia in 2017 was 3rd highest in Southeast Asia. The Banjarnegara District in 2018 was ranked with the third highest maternal mortality rate in Central Java Province. In previous years, the most common cause of maternal death in the district was bleeding, but in 2021 the biggest cause was COVID-19. This study aims to examine cases of maternal mortality by analyzing maternal characteristics, causes, and health service coverage from 2019 to 2021. Methods: The design of this study is a descriptive epidemiological study of maternal death cases in Banjarnegara in 2019-2021 using secondary data from the district health office. In-depth interviews with health workers in the public health center and the district health office. Results: Maternal death cases in 2019-2021 were 81 cases. COVID-19 will be the leading cause of maternal death during the COVID-19 pandemic in 2021, accounting for 60%. Conclusion: Preeclampsia was the leading cause of maternal death before the COVID-19 pandemic, while COVID-19 infection emerged as the primary cause in 2021. Strategic measures are needed to increase access to well-coordinated health services to reduce maternal deaths related to COVID-19 and the other effects of the pandemic.